Macrocycle-supported titanium complexes with chelating imido ligands: analogues of ansa-metallocenes. - Male, N; Skinner, M; Bylikin, S; Wilson, P; Mountford, P; Schröder, M (2000)
Reactions of 1,4-dimethyl-1,4,7-triazacyclononane (L1a) and 1,4-diisopropyl-1,4,7-triazacyclononane (L1b) to form 1-aminopropyl-4,7-di-R-1,4,7-triazacyclononane [R = Me (H2L3a) or Pri (H2L3b)] and 1-(2-aminobenzyl)-4,7-di-R-1,4,7-triazacyclononane [R = Me (H2L5a) or Pri (H2L5b)] are reported. Reaction of H2L3a and H2L5a with [Ti(NMe2)2Cl2] gives the ansa-linked macrocycle-imido complexes [Ti(kappa 4-L3a)Cl2] (5a) and [Ti(kappa 4-L5a)Cl2] (6a), respectively, and NHMe2. Reaction of H2L3a with [Ti(NBut)Cl2(py)3] gives [Ti(NBut)(kappa 3-H2L3a)Cl2] (7), which possesses a pendant alkylamine group that does not undergo amine/tert-butylimido group exchange to give 5a and ButNH2. However, reaction of H2L3b and H2L5b with [Ti(NBut)Cl2(py)3] does give amine/tert-butylimido group exchange to form [Ti(kappa 4-L3b)Cl2] (5b), [Ti(kappa 4-L5b)Cl2] (8b), and ButNH2. The compounds 5a,b and 6a,b are isolobal analogues of group 4 ansa-metallocene complexes and relatives of titanium cyclopentadienyl-amido constrained geometry olefin polymerization catalysts. Reaction of 5b with AgOTf affords [Ti(kappa 4-L3b)(OTf)Cl] (8) as the major product, the crystal structure of which has been determined. Alkylation of 6b by RLi gives the dialkyl derivatives [Ti(kappa 4-L5b)(R)2] [R = Me (9) or CH2SiMe3 (10)]. The ethylene polymerization capability of the compounds 5a,b, 6a,b, and 10 in the presence of methylaluminoxane has been determined and compared to that of [Ti(NBut)(kappa 3-L1a,b)Cl2] (11a,b); in all instances, low yields of high-molecular-weight polymer are obtained.